The economic impact of gunshot wounds on an urban level 1 trauma center. Issue 11 (November 2022) - Simske, Natasha M.; Rascoe, Alexander; Vallier, Heather A.
Highlights: Firearm-related injuries generate substantial morbidity and expense. Recidivism is common among this patient population, including 12% of the study cohort. Costs to the single facility were approximately $700, 000 (US dollars) per month, a modest amount of which was not compensated. Abstract: Introduction: Firearm-related injuries impact the healthcare system, taxpayers, and injured patients due to lost productivity and reduced quality of life. The goal was to quantify the economic costs related to hospitalization for gunshot wounds (GSWs) at a single urban level 1 trauma center. Materials and Methods: 941 patients over 27 months were treated for GSW. Elements related to hospitalization including length of stay, surgical procedures, medications and therapies, and subsequent readmission were identified, and costs were determined, inclusive of fixed and variable direct and indirect costs of facility care. Costs were classified based on body region: abdominal, chest, soft tissue, extremity or pelvic girdle, and head/neck/face. Results: Mean age was 30 years, with 94% male. Most patients (81%) were admitted, and 8% sustained fatal injuries. Overall, 12% were seen previously or subsequently for additional, unrelated GSWs. Mean costs per patient were: $66, 780 for abdominal GSWs; $3, 986 for chest; $3, 509 for soft tissue; $19, 875 for extremities; $64, 533 for head or neck, and means of $25, 249 for two regions and $26, 638 for three regions. Over the prospective period, 941 individuals sustained GSWs (approximately 35 per month). 37% were to the extremities, 23% were within the skin/subcutaneous tissue, 7% to the abdomen, 7% to the chest, 6% to the head or neck, and 20% to two or more body regions. Total facility costs for these 941 GSWs was $18.9 million, or $698, 960 per month. 55% of the patients had Medicaid, and 33% were uninsured, resulting in substantial uncompensated expenses for the trauma center. Conclusion: Firearm-related injuries generate considerable expense. Our data underestimated cost, as professional services and indirect costs associated with lost economic productivity of patients and caregivers were excluded. No objective assessment of the disastrous personal and social impact was projected. Moving forward, interventions to prevent initial injury and recidivism in this high-risk population are crucial. Level of Evidence: Level III